Protokol Keamanan pada Wireless Sensor Network (WSN) Menggunakan Firewall Iptables dan Enkripsi Base64 - Abdul Wahid; Satria Gunawan Zain; Jumadi Mabe Parenreng; Ilham Juliady (Progressive Information, Security, Computer, and Embedded System, 2024)
Currently, the era of technology is getting faster and more modern, such as the Internet of Things (IoT) system, most of which have been implemented in everyday life to facilitate every human activity. Such as the application of Wireless Sensor Network (WSN). Every public network service implementation has loopholes. This is very detrimental to companies that implement Wireless Sensor Network (WSN) system technology. If the server is hacked, the system data will be known by the hacker. For this reason, we need a way so that server security and data transfer processes are guaranteed. The method used is implementing an iptables firewall and encrypting data using Base64 encryption, where if this method is implemented then the server and any data sent in 2-way communication will be guaranteed safe from data reading and server hacking. So this method can be used to improve data security and server security.